An Overview of the Florida Bull Test - G. Cliff Lamb (EDIS)
AN227, a 3-page fact sheet by G. Cliff Lamb, describes this test designed as an educational aid for the improvement of beef cattle, its history since inception in 2000, and summarizes the consignors, bulls, breeds, performance, and sale averages of all previous Florida Bull Tests. Published by the UF Department of Animal Sciences, October 2009.